Kisspeptin Receptor GPR54 Promotes Adipocyte Differentiation and Fat Accumulation in Mice - Wang, Tongtong; Cui, Xueqin; Xie, Ling; Xing, Roumei; You, Panpan; Zhao, Yongliang; Yang, Yiqing; Xu, Yongqian; Zeng, Li; Chen, Huaqing; Liu, Mingyao (Frontiers in Physiology, 2018)
GPR54, Kisspeptin-1 receptor (KISS1R), a member of rhodopsin family, plays a critical role in puberty development and has been proposed to be involved in regulation of energy metabolism. This study aims to explore the function of GPR54 in adipogenesis, lipid metabolism and obesity in addition to its effect through hormones. Results showed that when fed a high-fat diet, the weight growth of castrated or ovariectomized Gpr54-/- mice was significantly slower than that of WT control, together with a lower triglyceride concentration. The ratio of white adipose tissue was lower, and average size of adipocytes was smaller in Gpr54-/- mice. Meanwhile, there were less adipose tissue macrophages, especially pro-inflammatory macrophages. Expression of inflammatory related genes also indicated that inflammatory response caused by obesity was not as drastic in Gpr54-/- mice as in WT mice. Liver triglyceride in Gpr54-/- mice was reduced, especially in female mice. On the other hand, oil drop formation was accelerated when hepatocytes were stimulated by kisspeptin-10. Primary mesenchymal stem cells of Gpr54-/- mice were less likely to differentiate into adipocytes. When stimulated by kisspeptin-10, 3T3-L1 cell differentiation into adipocytes was accelerated and triglyceride synthesis was significantly promoted. These data indicated that GPR54 could affect obesity development by promoting adipocyte differentiation and triglyceride accumulation. To further elucidate the mechanism, genes related to lipid metabolism were analyzed. The expression of genes involved in lipid synthesis including PPARγ, ACC1, ADIPO and FAS was significantly changed in Gpr54-/- mice. Among them PPARγ which also participate in adipocyte differentiation displayed a marked reduction. Moreover, phosphorylation of ERK, which involved in GPR54 signaling, was significantly decreased in Gpr54-/- mice, suggesting that GPR54 may promote lipid synthesis and obesity development by activating MAP kinase pathway. Therefore, in addition to the involvement in hormone regulation, our study demonstrated that GPR54 directly participates in obesity development by promoting adipocyte differentiation and fat accumulation. This provided evidence of involvement of GPR54 in lipid metabolism, and revealed new potentials for the identification and development of novel drug targets for metabolic diseases.